Recurrent and Prolonged Infections in a Child with a Homozygous IFIH1 Nonsense Mutation - Zaki, Maha; Thoenes, Michaela; Kawalia, Amit; Nürnberg, Peter; Kaiser, Rolf; Heller, Raoul; Bolz, Hanno J. (Frontiers in Genetics, 2017)
In an Egyptian girl born to consanguineous parents, whole-exome sequencing (WES) identified a homozygous mutation in PHGDH, c.1273G>A (p.Val425Met), indicating 3-phosphoglycerate dehydrogenase deficiency. This diagnosis was compatible with the patient’s microcephaly, severe psychomotor retardation, seizures and cataracts. However, she additionally suffered from recurrent (at least monthly) episodes of prolonged and severe chest infections requiring hospitalization, indicating a secondary, predisposing and potentially Mendelian, condition. A local reactivation of an EBV infection in the respiratory tract was detected after a recent chest infection, likely representing an opportunistic infection based on a compromised immune system. Further inspection of WES data revealed a homozygous nonsense mutation, c.2665A>T (p.Lys889*), in IFIH1, encoding MDA5. MDA5 detects long viral double-stranded RNA that is generated during replication of picorna viruses, and thereby activates the type I interferon signaling pathway. We propose that, analogous to severe course of primary influenza infection due to biallelic deficiency of a downstream effector, IRF7, homozygous loss of IFIH1 defines a novel Mendelian immunodeficiency disorder that increases susceptibility to severe viral infections. This is contrasted to heterozygous gain-of-function IFIH1 mutations in autoimmune diseases. Our findings highlight the potential of comprehensive genomic investigations in patients from consanguineous families to identify monogenic predispositions to severe infections.